Online learning during the COVID-19 pandemic: the wellbeing of Chinese migrant children—a case study in Shanghai - Ding, Qifan; Wu, Qiaobing; Zhou, Qi (Frontiers in Psychology, 2024)
Introduction This study uses Bronfenbrenner’s bioecological model as its theoretical framework to consider the findings of an investigation of the emotional, social, and physical wellbeing of Chinese migrant children and lessons learned from the COVID-19 pandemic in urban areas. This study expands our perspective by combining the views of students, parents, and teachers to explore the emotional, social and physical wellbeing of migrant children in Shanghai who were participating in online learning during the COVID-19. Methods Observation and semi-structured interviews were carried out to collect data for this case study. Thirty-one migrant children, nine parents, 10 teachers and a school principal from a Shanghai junior high school participated in this research. Qualitative data were analyzed using thematic analysis. Results and Discussion The findings indicated that although video-recorded lessons were high quality, it put pressure on migrant children due to the lessons containing only new material with no reviews and reduced opportunities for them to interact with their own teachers. In addition, the differences in study progress between the migrant children and the local children that showed up during the online learning, and neglect from teachers and policymakers, made the migrant children anxious, angry and confused about their future. Besides, parents install monitors at home to support their children’s online learning, but it had the opposite effect and simply provoked increased conflicts between children and their parents. Finally, although the online lessons have affected the optical health of students, the subsequent additional cooking lessons have mitigated the optical health problem and strengthened the connections between home and school. Conclusion The inequalities of education encountered by migrant children during the COVID-19 period have made them realize the disparities they have suffered in Shanghai. The exposure of this problem raises the prospect of a reform of educational policies for migrant children in the future.